Multi‐center experience of robot‐assisted laparoscopic para‐aortic lymphadenectomy for staging of locally advanced cervical carcinoma. (10th May 2013) - Fastrez, Maxime; Goffin, Frédéric; Vergote, Ignace; Vandromme, Jean; Petit, Philippe; Leunen, Karin; Degueldre, Michel
Abstract Objectives FIGO classification is commonly used for staging of locally advanced cervical cancer. Laparoscopic para‐aortic lymphadenectomy is currently used as a diagnostic tool, since we know that presence of para‐aortic lymph node metastases identifies patients with poor prognosis. The application of robotics during this procedure needs to be investigated. Design Retrospective multi‐center study. Setting Three centers participated in building one database. Population Thirty‐seven patients with locally advanced cervical cancer underwent a robot‐assisted laparoscopic para‐aortic lymphadenectomy. Methods Patients were prospectively enrolled in one register. Retrospective analysis of the whole database was performed. Main outcome measures Surgical outcomes of the robot‐assisted procedure and follow‐up data. Results Median number of lymph nodes collected was 27.5 (1–54) per patient. Five of 37 patients had para‐aortic node metastases. The false negative rate for PET‐CT diagnosing para‐aortic node metastases was 11.4% (4/35). Two major intra‐operative complications occurred (5.4%). Postoperative morbidity was low (13.5%). Median follow‐up was 27 months [95% confidence interval (95% CI) was 24–30]. Median disease‐free survival was 16 months (95% CI 2.4–29.6). Patients with negative nodes had a median disease‐free survival of 24 months (not assessable), although patients with positive nodes had a median disease‐free survival of 9 months (95% CI 6.9–11.9). Conclusions In this series we report that robot‐assisted laparoscopic para‐aortic lymphadencetomy provided the surgeon with useful information, diagnosing 11.4% of occult para‐aortic lymph node metastases in women with locally advanced cervical cancer. Intra‐operative and postoperative morbidity were low. The presence of para‐aortic lymph node metastases correlated with shorter disease‐free survival.